Comparison of recovery of sheep, goats, and calves from reversible electrical head-only and head-to-body stunning for halal meat production. - Beausoleil NJ; Farouk MM; Webster J; Johnson CB; Dowling S; Sazili AQ; Cameron C (Taylor and Francis Group, 2024)
Aims To compare the recovery of lambs, goats, and calves from head-only (HO) or high-frequency head-to-body stunning and evaluate the complementary use of behaviour and electroencephalography (EEG) to assess return to consciousness after electrical stunning in these species. Methods Six-month-old lambs, adult goats and calves (< 7 days old) were subjected to reversible head-only stunning (50 Hz, 1 A, 2 seconds) or reversible high-frequency head-to-body stunning (RHTB: HO followed by 2,000 Hz, 2 A, 4-second stun to body). Following stunning, behavioural recovery was assessed in 21 lambs, 22 goats, and 20 calves. Latencies to first perform behaviours (end of convulsions, head lift, attempt to right, successful righting, attempt to stand, successful standing) after stunning were scored from video recordings. Recovery of electrical brain activity indicative of consciousness was assessed using EEG in a separate cohort of minimally-anaesthetised lambs, goats and calves (n = 20 per species). EEG traces collected before and after stunning were classified as normal, epileptiform, isoelectric, or transitional activity. Following stunning, the duration of epileptiform and isoelectric activity combined (states of brain activity incompatible with conscious awareness) was calculated, as was latency to return of normal (pre-stun) EEG. Results The RHTB stun was reversible in all three species, although one sheep failed to recover and was euthanised. Both methods caused tonic and clonic convulsions in all species. Behavioural recovery of sheep and calves was similar for both methods while goats took longer to recover from RHTB than HO stunning. There was no evidence of differences between methods in the duration of EEG incompatible with consciousness or the latency to recovery of normal EEG. Conclusions Head-to-body stunning as applied here produced a reversible electrical stun in lambs, adult goats and young calves, although the benefits in terms of meat quality and operator safety are uncertain. Goats took longer to recover behaviourally from head-to-body stunning, possibly due to disrupted motor function, but there was no indication that post-stun unconsciousness lasted longer than following head-only stunning in any species. The normal behaviour for the animals’ developmental age should be considered when deciding on behavioural indicators of recovery. The minimal anaesthesia model provided excellent quality EEG data that was valuable for interpretation of the behavioural responses. Clinical relevance For the purposes of pre-slaughter stunning of sheep, goats and young calves, recovery appears comparable between the two methods, with all but 1/63 animals in the behaviour study recovering normal function.
Keywords: Electrical stunning; animal behaviour; animal welfare; electroencephalogram; halal